1991
DOI: 10.3109/02770909109073385
|View full text |Cite
|
Sign up to set email alerts
|

Parental Smoking and the Risk of Childhood Asthma

Abstract: In order to explore the correlation between parents' smoking habits and bronchial asthma in children, we undertook a cross-sectional study of 3300 (54% males, 46% females) school children aged 7-12 years old. A survey of smoking habits and attitudes conducted in Saudi Arabia showed a positive correlation between parental smoking and asthma. This study showed a significant link between parental smoking and chest wheeze or whistling, cough, and family history of rhinitis. Evidence is accumulating that there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Other studies have also found significant associations between persistent cough and parental smoking [2,13,22] between bronchial asthma and parental smoking [6,8,11,12,14,15,17,23,24]. Our demonstration that passive smoking significantly affects wheezy bronchitis is consistent with results obtained in a representative survey of schoolchildren in different parts of the world [1,6,11,17,18,25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Other studies have also found significant associations between persistent cough and parental smoking [2,13,22] between bronchial asthma and parental smoking [6,8,11,12,14,15,17,23,24]. Our demonstration that passive smoking significantly affects wheezy bronchitis is consistent with results obtained in a representative survey of schoolchildren in different parts of the world [1,6,11,17,18,25].…”
Section: Discussionsupporting
confidence: 91%
“…However, a few studies have included all four symptoms of wheeze, cough, asthma and bronchitis [18,24]. In this study we have included all four symptoms of wheeze, cough, asthma, and bronchitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have investigated the levels of passive smoking [12][13][14] in children. Murray and Morrison [20] compared the lung function of 247 children of mothers whose smoking habits were recorded by questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al [13] reported that passive smoking was positively associated with emergency room visits by asthmatic children. More recently Bener et al [14] undertook a cross-sectional study of 3300 school children and reported a significant link between parental smoking and asthma. A similar observation was reported independently by Martineze/ al.…”
Section: Introductionmentioning
confidence: 99%